(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2012)
The article analyzes the purpose and place of programming in school computer science course, conducted evaluating the advantages and disadvantages of using the programming language Pascal in general and different programming environments the language in particular.